2019
DOI: 10.1503/cmaj.190313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical networks: enablers of health system change

Abstract: KEY POINTS• The federal Advisory Panel on Healthcare Innovation noted the importance of innovation in health care and that most health care systems lack the ability to scale and spread innovation.• Some health systems have created system-wide clinical networks that identify priorities, explore solutions and implement strategies to improve care and outcomes.• Early evaluations suggest that clinical networks can improve care processes and enable system-wide change.• Successful networks have effective leadership,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Strategic Clinical Networks are partnerships between clinicians and consumers organized by disease area that identify priorities, explore solutions and implement strategies to improve care and outcomes. 10 5. As of 2012, pharmacists were allowed to bill for providing comprehensive annual care plans and ongoing disease management to patients with selected chronic diseases or for modifying or prescribing medications as the prescriber of record (www.ab.bluecross.ca/pdfs/pharmacy-benefacts/346 -compensation-for-pharmacy-services.pdf).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategic Clinical Networks are partnerships between clinicians and consumers organized by disease area that identify priorities, explore solutions and implement strategies to improve care and outcomes. 10 5. As of 2012, pharmacists were allowed to bill for providing comprehensive annual care plans and ongoing disease management to patients with selected chronic diseases or for modifying or prescribing medications as the prescriber of record (www.ab.bluecross.ca/pdfs/pharmacy-benefacts/346 -compensation-for-pharmacy-services.pdf).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] We conducted this study to define the ecology of medical care in Alberta and to examine whether it changed after 5 pol-icy changes were implemented province-wide by the health ministry and Alberta Health Services between 2003 and 2012 (Box 1). [8][9][10][11] We also explored the care received by subgroups defined by demographic characteristics, area of residence and whether patients had ambulatory-care-sensitive conditions (ACSCs), defined by the Canadian Institute of Health Information as asthma, chronic obstructive pulmonary disease, heart failure, coronary disease, hypertension, diabetes or epilepsy. 12 The ecology of medical care for adults in Alberta, 2002/03 to 2016/17: a retrospective cohort study the 2016 edition of the Canadian Community Health Survey 13 (a random survey of community-dwelling adults that is anonymous and thus not linked to their health records) and the Alberta Health Link teletriage database for 2018 (prior years did not have complete data capture).…”
mentioning
confidence: 99%
“…Patient and stakeholder engagement, leadership support, strategic alignment, funding partnerships and rigorous evaluation are important enablers, and provinces should evaluate the unique opportunities and barriers that exist within their local context. 4 The SCNs will continue to build and strengthen relationships with patients and community, academic, health and industry partners, locally and outside the province, having identified areas of focus for the next 5 years that reflect lessons learned, stakeholder feedback, shared priorities and current opportunities to advance improvement and transformation in the health system. 8 Improving coordination and alignment across SCNs and among network stakeholders, sharing best practices, and ensuring rigorous measurement and reporting are expected to be pivot al in further increasing the networks' effect and progress in supporting a learning, high-performing health system.…”
Section: Support Of Our People and Processesmentioning
confidence: 99%
“…Qualitative reviews of clinical networks in Scotland, the United Kingdom and Australia have shown that they evolved substantially over time in terms of network structure, processes and capabilities. 4 Alberta's experience reflects a similar evolution and strengthening of network capabilities. 4,5 This process of maturation is important because networks do not typically deliver improvements in health outcomes or savings to the health system in their first 2 to 3 years.…”
mentioning
confidence: 97%
See 1 more Smart Citation